(untitled) (Analysis in Theory and Applications, 2018)
We study here L^1-convergence of new modified double cosine trigonometric sum and obtain a new necessary and sufficient condition for L^1-convergence of double cosine trigonometric series. Also, the results obtained by Moricz[1],[2] are particular cases of ours.